Cardiovascular risk assessment using LOX-index and Self-Rating Depression Scale. (September 2016) - Inoue, Nobutaka; Fukuyama, Kazue; Hirayama, Sonoko; Yoshioka, Takayuki; Ozawa, Toru; Iwata, Sachiyo; Takei, Asumi
Abstract: Objective : LOX-Index is a novel biomarker for cardiovascular disease (CVD) and is calculated by multiplying LOX-1 ligands containing apolipoprotein B (LAB) and soluble LOX-1 (sLOX-1). The Framingham risk score (FRS) is a common clinical tool for risk assessment of coronary artery disease. Mental stress can also be an important risk factor for CVD. The purpose of this study was to examine the relationship between LOX-Index and FRS or mental stress. Methods: LOX-Index was measured in 453 subjects including 150 consecutive outpatients with lifestyle-related diseases such as diabetes, hyperlipidemia, and hypertension and 303 healthy volunteers. Mental stress was evaluated by the Self-Rating Depression Scale (SDS). Results: LOX-Index was significantly related with the 10-years risk of FRS. Multiple regression analysis demonstrated that LAB was closely associated with the smoking status, low-density lipoprotein (LDL), and high-density lipoprotein (HDL). There were no significant associations between LOX-Index and the SDS scores; however, by simultaneously using LOX-Index and SDS, the subjects could be classified in terms of oxidative stress and mental stress. Conclusions: LOX-Index appears to be a comprehensive marker that could evaluate the status of multiple CVD risk factors. The classification with LOX-Index and SDS could contribute to the risk assessment for CVD.